Effect of grain boundary engineering on the microstructure and mechanical properties of copper containing austenitic stainless steel - Sinha, Subhasis; Kim, Dong-Ik; Fleury, Eric; Suwas, Satyam (ELSEVIER SCIENCE SA, 2015)
The present investigation deals with grain boundary engineering of a modified austenitic stainless steel to obtain a material with enhanced properties. Three types of processing that are generally in agreement with the principles of grain boundary engineering were carried out. The parameters for each of the processing routes were fine-tuned and optimized. The as-processed samples were characterized for microstructure and texture. The influence of processing on properties was estimated by evaluating the room temperature mechanical properties through micro-tensile tests. It was possible to obtain remarkably high fractions of CSL boundaries in certain samples. The results of the micro-tensile tests indicate that the grain boundary engineered samples exhibited higher ductility than the conventionally processed samples. The investigation provides a detailed account of the approach to be adopted for GBE processing of this grade of steel. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: DESIGN; CHARACTER; NETWORKS